Formal guarantees of the independence of the constitutional judiciary in federal systems (Damascus University Journal for legal sciences, 2024)
This research is concerned with studying the formal guarantees of the independence of the constitutional judiciary in federal systems, and aims to shed light on the effectiveness and efficiency of the constitutional judiciary in protecting the federal system of the state, as it is the constitutional guardian of the principle of power-sharing between the two levels of government, by ensuring the accuracy of the application of the competencies distributed between the government. Federal and state governments. Therefore, federal constitutions are keen on the necessity of defining several guarantees that would preserve the independence of the constitutional judiciary.This study reached a number of results, namely: the necessity for the constitution to include a detailed organization of the mechanism forforming the constitutional court, specifying its competencies and the term of membership of its members, as this is one of the basic tasks of the constitution to guarantee his highness, so that the matter of organizing this body does not refer all or part of it to the control of the authority The competent authority to appoint, whether it is the legislative authority alone or the executive authority, given that these two authorities are subject to the control of this court, and therefore this court will be devoid of the minimum guarantees that guarantee its independence.The study also made some recommendations, including: The necessity of amending the text of Article (92) of the permanent Iraqi constitution, which referred the order organizing the Federal Court to the ordinary legislator, so that this amendment includes a detailed organization of this court. The study also recommended the need to pay attention to an issue that is a loophole surrounding the UAE constitution and would be a means of pressure that may be exercised with regard to judges who are not citizens of the Union, by not renewing those whose contracts have expired, or at least threatening not to renew them, as a tool to pressure them and force them to Adopting the directions of the central government, which violates the principle of the independence of the Federal Supreme Court.
Keywords: constitutional judiciary; federal systems; independence of the constitutional court; formal controls